Feeling Media : Potentiality and the Afterlife of Art - Sas, Miryam (Book collections on Project MUSE., 2022)
"In Feeling Media, Miryam Sas draws on experimental animation, postwar media theory, photography, and contemporary visual art to explore the potentialities and limitations of media theory and media art in Japan. The book aims to open media studies and affect theory to deeper engagement with works and theorists outside Euro-America by offering a detailed exploration of the critical discourses and artistic practices of both influential as well as lesser-known theorists and artists. Through case studies, Feeling Media proposes an emergent framework of analysis for the humanities that the author terms the "affective scale." The book reads Japanese media theory as working thought, taking into account its complexity and global interconnectedness while resisting reductive linkages to dominant Euro-American theory. The book also performs a historiographic experiment, viewing two key periods of rapid media transformation in relation to one another, while attending to disparities and disjunctures between them"--